Platelet Accumulation on Collagen: Drugs Which Inhibit Arachidonic Acid Metabolism and Affect Intracellular Cyclic AMP Levels - Adams, G A; Feuerstein, I A (Thrombosis and Haemostasis, 1984)
We have studied the accumulation of washed platelets on collagen-coated glass from flowing platelet-red blood cell suspensions in the presence and absence of drugs. Glass tubes were 10 cm long and the flow rate was 1 ml/min, 80 s-1. For all experiments, platelet accumulation was greatest near the tube’s inlet with a continuous decrease to the exit. A common feature, of those drug treatments which lead to reduced accumulation at the inlet, was an increase in outlet accumulation when compared with outlet control values. Platelet-collagen adhesion resulted in maximal release of 3H-serotonin in the presence of agents that prevent platelet aggregation on collagen. Only drug treatment known to raise cAMP levels (PGE1 and dipyridamole) or prevent the formation of prostaglandins and thromboxanes (sulfinpyrazone, indomethacin and ASA) were found to inhibit aggregate growth. Platelet aggregation on collagen in the absence of thrombin likely proceeds through the liberation of prostaglandins and thromboxanes from surface-bound platelets into the flow where they may stimulate flow-bom cells. An alternate hypothesis is that such treatments affect the release of a-granule components necessary for aggregation.
Keywords: Platelet adhesion; Platelet aggregation; Platelet release; Collagen; Anti-thrombotic drugs